Perubahan Budaya Komunikasi Dalam Penggunaan Media Sosial Tik Tok (Studi Mahasiswi IAIN Bukittinggi Di Kos Putri Al Maizy, Gurun Aua, Kubang Putiah) - Sri Mulyani; Syafwan Rozy (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
Cultural changes will continue to develop in every era, with the emergence of new technologies, one of which is social media. Social media aims to provide convenience in terms of communicating so that it has an impact on its users, both positive and negative. One of the most widely used applications from other social media is the Tik Tok application where each user can make various videos and interact via private chat. The app, launched in September 2016, shows how important its influence on culture is. Where tick tock has become the most widely used social media, one of which is among students. The purpose of this study was to find out the factors that cause changes in the culture of communication and how changes in the culture of communication in the use of social media tick tok by IAIN Bukittinggi students who live in Al Maizy's boarding house, Gurun Aua Nagari Kubang Putiah.